Marriage in Indonesia: a systematic literature review of key issues in Scopus-indexed journals - Fawaiq Sayyaf, R. Tanzil; Anggraeni, Luciana; Aydin, Elif (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
Marriage is a significant and complex topic in Islamic family law, influenced by various legal, social, and cultural factors. In Indonesia, where the majority of the population is Muslim, Islamic marriage law holds an essential position. However, the dynamics of marriage in Indonesian Muslim society have faced new challenges due to rapid social changes, globalization, and technological advancements. This study aims to systematically map the predominant themes and emerging issues in marriage research within accredited Islamic family law journals through a Systematic Literature Review (SLR). The research questions focus on: (1) What are the dominant trends in publications on marriage in Indonesia in Scopus-indexed journals? (2) What research methods have been used? (3) What novel issues remain underexplored? To answer these questions, this study employs SLR methodology, using the PRISMA framework to filter and analyze relevant literature from 2010 to 2025. A total of 86 articles were selected from various international, Scopus-indexed journals, synchronized with Zotero reference manager and visualized using VosViewer and R Studio for keyword mapping and trends. The findings indicate that research on marriage in Indonesia has predominantly been qualitative, focusing on normative-juridical aspects such as legal frameworks and doctrinal interpretations. The most frequently discussed issues include child marriage, interfaith marriage, polygamy, and the legal age of marriage, often analyzed from legal, social, and religious perspectives. However, the study also identifies research gaps, particularly in empirical studies exploring the practical implications of marriage policies and social realities. This study provides a comprehensive mapping of dominant themes and underexplored research areas, serving as a foundation for future research and policy-making in Islamic family law. In a nutshell, This study concludes that research on marriage in Indonesian Islamic family law has been dominated by normative-juridical approaches, focusing on themes such as child marriage, interfaith marriage, polygamy, and the legal age of marriage. While these studies provide important doctrinal insights, they reveal a lack of empirical and interdisciplinary research that examines the practical implications of marriage policies in society. Future research should bridge this gap by employing socio-legal and empirical approaches, exploring underexamined issues for instance, technological influences, gender justice, and comparative perspectives, thereby enriching both academic discourse and policy development in Islamic family law.